2022
DOI: 10.3390/ma15207315
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Metasurfaces on Building Construction Materials for Potential Electromagnetic Applications in the Microwave Band

Abstract: Energy self-sufficiency, as well as optimal management of power in buildings is gaining importance, while obtaining power from traditional fossil energy sources is becoming more and more expensive. In this context, millimeter-scale metasurfaces can be employed to harvest energy from microwave sources. They can also be used as sensors in the microwave regime for efficient power management solutions. In the current study, a simple spray printing method is proposed to develop metasurfaces in construction material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Particularly, metasurfaces were measured using a combination of a P9372A Vector Network Analyzer (VNA) (Keysight, California, USA; frequency range: 300 kHz–9 GHz) and waveguides WR284 (2.4–4.8 GHz), WR187 (3.5–7 GHz), and WR137 (5–10 GHz) (Figure c), so that a frequency range of 2–9 GHz was covered. Details regarding the setup and the measurement procedure were previously described. ,, Two different configurations were investigated, i.e., the CSRR is oriented so that the electric field component is parallel (TE orientation, drawing in Figure a) and perpendicular to the gap (TM orientation, drawing in Figure c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, metasurfaces were measured using a combination of a P9372A Vector Network Analyzer (VNA) (Keysight, California, USA; frequency range: 300 kHz–9 GHz) and waveguides WR284 (2.4–4.8 GHz), WR187 (3.5–7 GHz), and WR137 (5–10 GHz) (Figure c), so that a frequency range of 2–9 GHz was covered. Details regarding the setup and the measurement procedure were previously described. ,, Two different configurations were investigated, i.e., the CSRR is oriented so that the electric field component is parallel (TE orientation, drawing in Figure a) and perpendicular to the gap (TM orientation, drawing in Figure c).…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding the setup and the measurement procedure were previously described. 55,56,60 Two different configurations were investigated, i.e., the CSRR is oriented so that the electric field component is parallel (TE orientation, drawing in Figure 2a) and perpendicular to the gap (TM orientation, drawing in Figure 2c).…”
Section: Metasurface Electromagnetic Characterizationmentioning
confidence: 99%
“…Z. Viskadourakis et al [38] proposed a method to develop metasurfaces in construction materials (plasterboard and wood). He showed that application of electromagnetic sprayprinted MS, integrated on construction materials with larger areas (such as walls or doors) can potentially be used for EM applications, for buildings, for power self-efficiency, and for management.…”
Section: Energy-efficient Buildingsmentioning
confidence: 99%
“…Although spray deposition using conductive paint has been previously demonstrated for transmissive metasurfaces [33], this paper reports the first rapidly prototyped aerosol spray deposited liquid-metal anomalous reflective metasurface. Using a pressurized air gun and a plastic thin-film mask, liquid metal is patterned on a substrate, with an The liquid metal used here is Galinstan (Rotometals Incorporated, San Leandro, CA, USA), a near eutectic gallium-based alloy consisting of Ga 68.5 wt%, In 21.5 wt%, Sn 10 wt%.…”
Section: Introductionmentioning
confidence: 98%